2014
DOI: 10.3109/09540261.2014.927753
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders as a public health issue: Prevalence and attributable impairment of quality of life in an Italian community sample

Abstract: The prevalence of eating disorders (ED) in the community is still under debate, as well as the measure of their impact on the well-being of individuals. It was decided to evaluate the prevalence of eating disorders in an Italian community sample as well as to measure the burden of the quality of life of people and to compare it to those attributable to other chronic illnesses. A community survey of 4,999 people using a questionnaire on health services utilization, the Advanced Neuropsychiatric Tools and Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
0
34
1
3
Order By: Relevance
“…People with eating disorders have low quality of life, and early detection is associated with better treatment outcomes . We hope that the availability of these data will improve understanding of male body image concerns and disordered eating and hence lead to increased detection of EDs in primary care settings and the development of validated treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with eating disorders have low quality of life, and early detection is associated with better treatment outcomes . We hope that the availability of these data will improve understanding of male body image concerns and disordered eating and hence lead to increased detection of EDs in primary care settings and the development of validated treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Eating disorders (EDs) represent a challenge to public health in terms of psychiatric comorbidity and functional impairment, and because they affect the quality of life of affected individuals and their caregivers . However, only a few affected individuals seek professional help, perhaps partly due because of the difficulties of detecting and referring patients in primary care settings . EDs are also classically considered a typically female pathology; consequently, disordered eating and body image concerns in men tend to be underestimated, misunderstood, and undertreated .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies using interviews did not report overall ED rates, but rather diagnose specific rates (see Table 1). However, where interview-based ED prevalence was reported, lifetime prevalence was most commonly listed, with rates for females and males ranging from 1.0% 73 to 2.6%, 56 and from 0.3% 73 to 0.6%, 56 respectively. Finally, in studies employing selfreports, all studies reported point prevalence with overall EDs rates ranging from 1.2% 78 to 13.4% 79 in females, and 1.1% 76 to 4.3% 87 in males.…”
Section: Prevalencementioning
confidence: 99%
“…Eating disorders (EDs) and their associated levels of impairment, morbidity, and cost are a significant public health concern (Brownell & Walsh, ; Carta, Preti, & Moro, ; Crow, ; Hudson, Hiripi, Pope, & Kessler, ). Although EDs affect people of all demographics, research indicates that some populations are at increased risk for developing EDs (Brownell & Walsh, ).…”
Section: Introductionmentioning
confidence: 99%